Non-linear effects of heterogeneous environmental regulations on green growth in G20 countries: Evidence from panel threshold regression - Wang, Xiaoling; Shao, Qinglong (The Science of the total environment, 2019)
A comprehensive understanding of the relationships between environmental regulations and green growth of economy is essential for policy design and decision-making. This paper combines hybrid measure with Global Malmquist Luenberger index to estimate national green growth level. A panel threshold regression technique is then employed to observe the non-linear impacts of both the formal and informal environmental regulations on green growth in Group 20 countries during 2001–2015. Results from empirical tests reveal that, for the formal environmental regulations represented by Environmental Policy Stringency (EPS), the market-based EPS is only significant at high-level phase while this is not the case in the low-level counterpart; non-market based EPS witnessed significant signs across the three phases, but in varied coefficients and significance levels. By comparison, the informal environmental regulations represented by environmental-related technologies and education levels show positive and significant impact on green growth, except for the case when countries have higher level of technologies. In addition, income per capita and gross Research & Development (R&D) expenditures present significant positive impacts on the dependent while share of service sector to the economy and investment on transport infrastructure witnessed negative effects across the models. Policy implications are proposed thereafter, although both the formal and informal environmental regulations are important to promote green growth, but they show different impacts at different phases. [Display omitted] •A global Malmquist Luenberger index has been employed to measure green growth.•Non-linear regulation-growth nexus has been examined by panel threshold model.•Environmental Policy Stringency show significant positive effects on green growth.•Education exerts larger impact on green growth than environmental-related technologies.